Language matters - Bauer, Laurie; Holmes, Janet; Warren, Paul. (New York: Palgrave Macmillan, 2006)
Language Matters provides an approachable introduction to the study of language, focusing on the questions that non-specialists often ask about the subject. Taking a non-technical approach, the book explores the core areas of language study and sets out to answer fundamental questions about the origin and development of languages, the structure of languages, how language interacts with social structures and how our
Includes bibliographical references and indexes.
Keywords: Language and languages